Tennis serve volume, distribution and accelerometer load during training and tournaments from wearable microtechnology - Perri, T.; Reid, M.; Murphy, A.; Duffield, R. (International Journal of Performance Analysis in Sport, 2024)
This study analysed the volume, intensity and distribution of tennis serving between (1) training and tournament mesocycles, and (2) within-mesocycle based on session-type, drill-type and week. Seven elite females wore a GPS device, with in-built accelerometer and gyroscope, during training and tournament mesocycles. Sessions were classified as "practice sessions" or "official matches" and drills as "serve-focused drills" or "point-play". Training weeks were classified according to their timing prior to tournaments ("Week -3", "Week -2" and "Week -1"). Machine learning algorithms detected serves from the raw accelerometer and gyroscope data to report serve count, load and rotation magnitude in absolute and relative (.min-1 or serve) values. Cohen`s d with 95% confidence intervals compared serve volume (count), intensity (serve load, rotation magnitude) and distribution (n.min-1) between session- and drill-type during mesocycles. Cumulative serve counts were compared between training weeks. Increased absolute serve load was observed during official matches compared to practice sessions (d = 0.97-1.07[0.69-1.30]). Serve-focused drills in training mesocycles have lower absolute counts and serve load (d = 0.82[0.54-1.34]), though greater relative count and load (d = 1.10-1.87[0.59-2.19]). Trivial-small ES existed between training weeks for cumulative serve count (d = 0.12-0.25[-0.83-1.27]). Session- and drill-level analyses highlight greater mechanical demands in official matches, though lower serve density in point-play.